2021
DOI: 10.1021/acs.joc.0c02542
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Potent Anticancer Substituted 5-Benzimidazol-2-amino Thiazoles Controlled by Bifunctional Hydrogen Bonding under Microwave Irradiations

Abstract: Benzimidazol-amino thiazoles are synthesized under microwave irradiations using benzimidazole phenyl thiourea and 2bromoacetophenone. Bifunctional hydrogen bonding plays an important role in chemical conversion. The reaction was carried out by C−C bond formation, followed by C−N bond cleavage and simultaneous migration of the benzimidazole ring. This reaction is novel and efficient for the synthesis of benzimidazol-amino thiazoles in which microwaves were used as driving forces. Synthesis of the product was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In continuation of our ongoing research forthe synthesis of the benzimidazole heterocyclic compounds with their mechanistic studies, [11] we focused on the synthesis of benzimidazol-2-imino diphenyl thiazolidin-4-ol (B1) hemiaminals (carbinolamine).This hemiaminal (B1) prepared by solid-phase reactive chromatography and utilized it as starting material in our recently published work [12] for the synthesis of 5-benzimidazol-2-iminodiphenyl thiazoles under microwave irradiations by the migration of the benzimidazole ring. The reaction was well controlled by bifunctional hydrogen bonding (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In continuation of our ongoing research forthe synthesis of the benzimidazole heterocyclic compounds with their mechanistic studies, [11] we focused on the synthesis of benzimidazol-2-imino diphenyl thiazolidin-4-ol (B1) hemiaminals (carbinolamine).This hemiaminal (B1) prepared by solid-phase reactive chromatography and utilized it as starting material in our recently published work [12] for the synthesis of 5-benzimidazol-2-iminodiphenyl thiazoles under microwave irradiations by the migration of the benzimidazole ring. The reaction was well controlled by bifunctional hydrogen bonding (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…The reaction was well controlled by bifunctional hydrogen bonding (Scheme 2). [12] The impressive result of this reaction envisaged that we can easily develop CÀ C bond formation reaction at guanidino carbon of benzimidazole ring. With the aim to explore the novelty in the chemistry of CÀ C bond formation at guanidine carbon of benzimidazole ring, we begin with N-tosylation on benzimidazole ring (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…The benzimidazole-thiazole hybrids exhibited considerable antiproliferative activity, [49][50][51][52] and among them, hybrid 19 (Figure 4; IC 50 : 2.4-12.0 µM, MTT assay) was active against HT-29, DU145, A549, and MDA-MB-231 cancer cell lines and the activity was comparable to that of doxorubicin (IC 50 : 1.8 µM) against A549 cells. [52] The SAR indicated that the introduction of hydrazine into thiazole moiety was permitted and hybrid 20 (IC 50 : 6.3 µM, MTT assay) was not inferior to erlotinib (IC 50 : 4.2 µM) against MCF-7 cells. [53] Mechanistically, hybrid 20 induced apoptotic effect and cell cycle arrest at the G2/M phase, upregulated caspase-3, p53, Bax/Bcl- (IC 50 : 2.1 µM) against HeLa cells.…”
Section: Benzimidazole-sulfone/ Sulfonamide Hybridsmentioning
confidence: 99%
“…shown a wide variety of biological activities such as anti-cancer [7][8][9], anti-bacterial [10][11], anti-fungal [12][13], anti-viral [14] anti-diabetic [15], anti-in ammatory [16,17] have others found application as liquid crystals [18], and used in cosmetic sunscreens [19], also used as anti-tubercular-agents [20], anticonvulsions [21] and also used as CDK2 inhibitors [22].…”
Section: Introductionmentioning
confidence: 99%